IDENTIFICATION OF FUNGAL SPECIES ASSOCIATED WITH THE SPOILAGE OF FRUIT IN DUTSIN-MA METROPOLIS, KATSINA STATE - Buah, J. D.; Eberemu, N. C.; Okeseni, O. (FUDMA JOURNAL OF SCIENCES, 2024)
The aim of this study was to isolate and identify the fungi species associated with spoilage of orange (Citrus sinensis); Banana (Musa acuminate); and Mango (Mangifera indica) fruit. A total of 30 fruit samples were collected from market in Dutsin-ma metropolis, the study was carried out between June to August, 2023. The samples were surfaced sterilized with ethanol and the homogenates were cultured on Potato Dextrose Agar and incubated aerobically at room temperature for 5days at 30°C. The pure cultures obtained were identified morphologically and microscopically using a standard mircrobial Atlas for verification. The fungal species identified from the isolates are Aspergillusspp, Candidaspp, Alternariaspp, Fusariumspp, Mucorspp, Rhizopusspp, Collectoricumspp, and Peniciliumspp. Aspergillusspp was the most predominant fungal specie isolated from orange (citrus sinensis) having a frequency of 60% followed by Candidasppand Alternaira with 20% prevalence. Fusariumspp was the most predominant fungal specie isolated from banana (Musaacuminata), having a frequency of (44%), followed by Mucorspp (33%) and Rhizopusspp (22%). Aspergillusspp was the most predominant fungal specie isolated from mango (Mangifera indica) having a frequency of (70%) followed by Collectoricumspp(20%) and Peniciliumspp(10%). Aspergillusniger was the most predominant isolates from all the fruits under study. These findings are indicative that fungal species are associated with the spoilage of orange, (Citrus sinensis), banana (Musa acuminata), and mango (Mangifera indica) fruit leading to economic loss and possible human health hazard as a result of consumption of spoilt fruits.
Keywords: Fungi; Fruit; Musa acuminate; Citrus sinensis; Mangifera indica